THE SECTION OF TORRE PICCHIO (TERNI, UMBRIA, CENTRAL ITALY):A VILLAFRANCHIAN SITE RICH IN VERTEBRATES, MOLLUSCS,OSTRACODS AND PLANTS (Rivista italiana di Paleontologia e Stratigrafia, 2003)
Fluvial deposits of the S. Maria di Ciciliano Formation crop out near Montecastrilli (Terni), in the southwestern branch of the Tiberino Basin.  Many specimens of plants ("mummified" woods, fruits and seeds), freshwater molluscs, ostracods, vertebrate bones and coprolites were collected at Torre Picchio. This small outcrop contains a fairly rich record of fruits and seeds, among which about 50 species were identified; the most frequent invariably belong to submerged, floating and emergent aquatic herbs, possibly because these were buried not far from their place of growth, thus representing the ancient local vegetation.  The fruits and seeds of woody plants, including several exotic elements, were transported from neighbouring areas and indicate a paleoclimate similar to the present day, though slightly wetter.  Among molluscs, three distinct assemblages were found, indicating fluvial, swampy and lacustrine environment, respectively.  They contain taxa of biochronological interest, most of them typical of Early Pleistocene deposits (late Villafranchian), but making their first appearance in the Late Pliocene (Middle Villafranchian). One species, Margarifera (Pseudunio) auricularia, represents the oldest record everywhere, since it was known, so far, only from the Middle Pleistocene upwards.  As palaeoenvironmental indicators, the ostracods complete the information given by molluscs.  Vetrebrates are represented by large and small mammals, rare birds, reptiles, amphibians and some fishes.  A great number of coprolites was collected as well.  The mammal assemblage shows affinities with the Costa S. Giacomo and Olivola F. U. (Middle and Late Villafranchian, Late Pliocene). Mimomys medasensis, an Iberoccitane element, is signaled for the first time in Italy.  From the geological point of view, the S. Maria di Ciciliano Fm. is interfingering with the marine Chiani-Tevere Fm., which is mostly Santernian in age and lies unconformably on the Middle Pliocene cycle. Only in some areas representing a structural low, the continuous transition between the lower portion of this unit and Late Pliocene deposits may be observed before the heteropic episodes.  This fact suggests some inconsistencies between chronostratigraphy and biochronology in the examined area because some taxa indicate a latest Pliocene age.  A heterochrony in the extinction of some species of plants and animals is suggested as a possible solution to the problem.